Implementation of Differentiated Learning Through Play Activities in Early Childhood - Ika Astuti; Achmad Ruslan Afendi (EduLine: Journal of Education and Learning Innovation, 2022)
This study aims to determine the activities of teachers in the implementation of differentiated learning through play activities in early childhood. This study uses a qualitative approach with a descriptive method. The instrument used is an observation sheet to observe the actions of teachers and students. Written guidelines and observations serve as research tools and these are processed through observation, interviews, and documentation. Data analysis is organizing data, presenting data, and drawing conclusions. This study was conducted in a kindergarten school. The school was chosen because the researcher is one of the school's teachers, thus facilitating the research process. This study is field research, so the information reviewed in this article is data that occurred at the research location. The results of this study indicate that the process of planning differentiated learning through play activities in early childhood has been carried out following the rules of learning planning in Early Childhood Education Programs (ECEP). Implementing differentiated learning through play activities in early childhood follows the principles of child development. Differentiated learning through play activities in early childhood has succeeded in optimizing aspects of children's cognitive, affective, and psychomotor development. It is proven from the results of the evaluation reports given by the school to the parents of students showing that the aspects of student development have developed well. This is also reinforced by reports from parents of students that there is a significant improvement in the development of children at home. The assessment is carried out by the teacher using instruments prepared by the school.